WASTE MANAGEMENT IN AGRICULTURE - Elena BONCIU; Ramona Aida PĂUNESCU; Elena ROȘCULETE; Gabriela PĂUNESCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Waste of any kind, resulting from many human activities, is a very topical issue, both due to the increase in quantities and types (which through degradation and infestation pose a danger to the natural environment and the health of the population) and significant amounts of materials, raw materials, reusable materials and energy that can be recovered and put into the economic circuit. Waste is not only an environmental problem, but also an economic loss. The types of waste resulting from agriculture and forestry are: vegetable waste and waste from preparation; waste from manure; waste from forest holdings; used motor oils; used tires; plastic waste, including plastic packaging waste; waste from batteries and accumulators. In Romania, of the total amount of waste generated, most is vegetable waste and waste from preparation (over 90%), according to the National Institute of Statistics. Waste management must be carried out in waste recovery or disposal facilities. Thus, waste from agriculture can be managed by: recovery of organic substances - biogas plants, composting, recycling of plastic waste; recycling of scrap metal; incineration - in the case of hazardous waste (agrochemical waste, used oils); storage - in the case of waste that cannot be recovered. The EU legislation, more exactly the Waste Framework Directive creates the framework in which waste management has to implemented regarding prevention, preparation for reuse, recycling, recovery and disposals. The Directive has the duty to prevent the greatest possible generation of waste, to utilize the waste generated as a resource and to diminish to a minimum the amount of waste that reaches landfills. In this way, environmental pollution can be significantly reduced. After all, waste can be a problem or a resource only depending on how it is managed.